Patient-Controlled Intravenous Analgesia for Advanced Cancer Patients with Pain: A Retrospective Series Study. (4th April 2018) - Peng, Zhiyou; Zhang, Yanfeng; Guo, Jianguo; Guo, Xuejiao; Feng, Zhiying
Abstract : Objective . To compare the efficacy and side effects of patient-controlled intravenous analgesia (PCIA) with hydromorphone, sufentanil, and oxycodone on the management of advanced cancer patients with pain. Methods . Patients allocated to receive PCIA between January 2015 and December 2016 were chosen for this study. After reviewing medical records, we verified if hydromorphone, sufentanil, or oxycodone for PCIA could equally provide effective pain relief. A numeric rating scale (NRS) of cancer pain was applied before PCIA, at 4 hours after PCIA, and at the discontinuation of PCIA. Secondary, the incidence of clinical side effects attributed to PCIA was observed. Results . A total of 85 medical records were reviewed. PCIA with hydromorphone (n = 30 ), sufentanil (n = 34 ), and oxycodone (n = 21 ) was used for cancer pain management. PCIA successfully improved pain control in 97.6% of the patients. The most common side effects were constipation (11.8%), nausea (8.2%), and sedation (5.9%). Drug addiction, delirium, or respiratory depression associated with PCIA was not reported in this case series study. No significant intergroup difference was observed in NRS at any of the abovementioned time points. There was no significant difference of analgesic effect among the hydromorphone, sufentanil, or oxycodone. Conclusion . PCIA provided timely, safe, and satisfactory analgesia for advanced cancer patients with pain and may be useful for titration of opioids, management of severe breakthrough pain, and conversion to oral analgesia. There was no significant difference of analgesic effect and side effect among the hydromorphone, sufentanil, and oxycodone.